TRPV4 activation prevents lipopolysaccharide-induced painful bladder hypersensitivity in rats by regulating immune pathways - Yoshizumi, Masaru; Tazawa, Naoya; Watanabe, Chizuko; Mizoguchi, Hirokazu (Frontiers in Immunology, 2022)
Abstract Chronic inflammation in the urinary bladder is a potential risk factor for bladder dysfunction, including interstitial cystitis/bladder pain syndrome (IC/BPS). Although several studies have reported that activation of transient receptor potential vanilloid 4 (TRPV4) contributes to bladder pain and overactive bladder with a cardinal symptom of acute or chronic cystitis, others have reported its involvement in the protective response mediated by lipopolysaccharides (LPS) to secrete anti-inflammatory/pro-resolution cytokines. Therefore, we investigated the potential benefit of an intravesical TRPV4 agonist for painful bladder hypersensitivity in a rat model of LPS-induced cystitis and determined whether its effects modulate the LPS signal for inflammatory reaction, cytokine release, and macrophage phenotype change. Previously, we showed that repeated intravesical instillations of LPS induce long-lasting bladder inflammation, pain, and overactivity in rats. In the present study, concurrent instillation of the selective TRPV4 agonist GSK1016790A (GSK) with LPS into the rat bladder improved LPS-induced bladder inflammation and reduced the number of mast cells. Furthermore, co-instillation of GSK prevented an increase in bladder pain-related behavior and voiding frequency caused by LPS. Cytokine profiling showed that LPS-stimulated inflammatory events, such as the production and secretion of pro-inflammatory cytokines (CXCL1, CXCL5, CXCL9, CCL3, and CX3CL1), are suppressed by GSK. Furthermore, TRPV4 activation switched LPS-stimulated pro-inflammatory M1-type macrophages to anti-inflammatory M2-type macrophages. These results suggest that TRPV4 activation in the bladder negatively regulates the pro-inflammatory response induced by LPS and prevents bladder hypersensitivity. These TRPV4 functions may be promising therapeutic targets for refractory IC/BPS.